(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The subject of the study deals with the role of the constitutional judiciary as a guarantee for the protection of basic rights and freedoms. The research was divided into two sections. In the first section, we reviewed the function of the constitutional judiciary through monitoring the constitutionality of laws, interpreting the constitution, the legitimacy of the constitutional judiciary, and the foundations of the constitutional judiciary. In the second section, the researcher referred to the constitutional mechanisms that guarantee rights and freedoms by reviewing the oversight of the constitutionality of laws that were entrusted to a judicial body that stands in the way of any violation or transgression of limits issued by public authorities during the exercise of their work. The study concluded that the constitutional texts establish the principles of rights and freedoms, and determine them based on a way that guarantees individuals’ enjoyment of it in the state of law and gives it a constitutional character.